Characterization of edible coating based on surimi fillet catfish as biodegradable packaging. (February 2019) - Saputra, E
Abstract: One of the problems that often arise in the fisheries sector is maintaining quality. At room temperature, the fish more quickly enter the phase of rigor mortis and last shorter. If the rigor phase can not be maintained for longer, then decay by enzymes and bacterial activity will take place more quickly. The retention of fresh fish can be extended by adding antibacterial compounds in the form of synthetic chemicals or natural ingredients. One of the safe natural ingredients used to extend the freshness of fish is an edible coating. Edible coatings may be hydrocolloid-based (proteins, polysaccharides), lipid-based (fatty acids, acyl glycerol, waxes or waxes) or composite (a mixture of hydrocolloids and lipids). Surimi in the food industry can be used as an ingredient to make edible packaging, or better known in the form of edible film and protein-based edible coating. Edible film and potential coatings are used as packaging materials as they can affect food quality, food safety, and product shelf life positively. Edible protein-based films (protein-based film and coating) have superior inhibitory and mechanical properties compared to polysaccharide-based ones.